ABOUT THE DISTANCE FUNCTION BETWEEN FUZZY SETS - Whaib, Sufyan A (Al-Nahrain Journal of Science, 2018)
In this paper, we will study and construct the distance function between two fuzzy sets in a fuzzy metric space and give an example to illustrate this function.